Effets civils et organisation conventionnelle de l'union homosexuelle - Allard, Serge (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1985)
The recent Family Law Reform in Quebec makes no mention of non-traditional unions. No formal legal regime regulates the economic responsibility of homosexual partners. The author studies the most flagrant pecuniary consequences of the inability of a homosexual couple to marry and explores the possible effects of such a union on the property rights of the partners. A contractual agreement that does not necessarily off end public order and good morals may appear to be a solution to the aspirations of certain couples.